Indirect improvement of pepino (Solanum muricatum) productivity via nitrogen fertilizer-mediated microbial and enzymatic stimulation - Su, Bingbing; Pei, Huaidi; Li, Shiweng; Ma, Zhongming; Chen, Yuliang; Li, Yubin; Wang, Liguang; Zhang, Minmin; Li, Zhongwang (Frontiers in Microbiology, 2025)
IntroductionTo meet the both escalating production requirements of pepino cultivation and maintaining soil sustainable development through precise exploration of chemical fertilizer input amounts.MethodsA 5-month greenhouse experiment evaluated how varying nitrogen fertilization rates (0, 75, 150, 225, and 300 kg⋅ha–1) modulate soil biochemical properties and their subsequent effects on pepino productivity and fruit nutrients components.ResultsOur study revealed that the N300 treatment maximized vegetative growth (plant height, leaf and fruit dry biomass), as well as plant nitrogen and fruit calcium contents, but significantly reduced root-to-shoot ratio, vitamin C, and soluble sugars versus N0. N225 optimally balanced productivity and nutrition, and elevated nitrogen use efficiency (34.13%), per plant yield (45.60%), fruit protein (142.68%) and calcium (32.72%). N150 showed intermediate benefits with peak stem dry biomass and sugar content, while N75 provided only marginal growth stimulation. Moreover, nitrogen fertilization differentially modified soil biochemical properties, N300 treatment markedly enhanced urease (143.24%), nitrate reductase (99.38%), and sucrase (23.87%) activities, while increasing the relative abundances of Nitrosomonas and Ensifer, though at the cost of reduced pH, nitrite reductase, and alkaline phosphatase activities. N225 treatment improved microbial ACE and Chao indexes, and enriched the Opitutus, but depleted available nitrogen (−29.53%) and available potassium (−27.90%). N150 boosted the relative abundance of Bacillus (45.15%), Arthrobacter (72.67%), Sphingomonas (57.55%), and enriched the Mesorhizobium. N75 had slightly positive effects on core genera and nitrogen cycling microorganism. Therefore, we recommend nitrogen application rates of 150 ∼ 225 kg⋅ha–1 to optimize pepino production. Moreover, the PLS analysis illustrated that nitrogen fertilization indirectly enhanced pepino productivity by stimulating urease and nitrate reductase activities, and enriching functional microbiota (Nitrosomonas, Opitutus, Ensifer, and Mesorhizobium) to facilitate soil nutrient mobilization (soil total nitrogen, available nitrogen and available potassium) for plant growth. Notably, fruit nutrients components (protein and calcium contents) were directly modulated by nitrogen application amounts.DiscussionOur research provided crucial theoretical foundations for both sustainable soil management and meeting the escalating production requirements in pepino cultivation.